Kontrribusi Keputusasaan (Hopelessness) terhadap Suicide Ideation pada Dewasa Awal di Sumatera Barat - Khairiyah, Salmaa; Ningsih, Yuninda Tria (Innovative: Journal Of Social Science Research, 2025)
Suicide is a global public health issue that needs more attention, especially in early adulthood with low economic conditions. Suicidal behavior is related to suicidal ideation. One of the factors of suicidal ideation is hopelessness. This study aims to measure how much hopelessness contributes to suicidal ideation in early adults who have had or are having suicidal ideation in West Sumatra. This study applies a correlational quantitative method and utilizes an accidental sampling technique as a sampling method. The subjects in this study were 349 early adult individuals in West Sumatra who have had suicidal ideation. The data collection method in this study is using the Beck Hopelessness Scale (BHS) and the Revised-Suicide Ideation Scale (R-SIS), which is then processed by applying simple linear regression data analysis techniques and utilizing the SPSS version 29 program. The significance value in this study is 0.001 < 0.05, which indicates that the alternative hypothesis (Ha) is accepted so that it can be concluded that there is a contribution of hopelessness to suicide ideation in early adults who have had or are having suicidal ideation in West Sumatra. The contribution of hopelessness to suicide ideation is 29.4%.